Spirituality we do not have such a Thing: Patrimonialization Processes as Minefields - Briones, Claudia Noemi (2017)
Three vignettes are used as points of departure to identify the dynamics of the politics of recognition of indigenous patrimony, in terms of the languages of contention enabled to struggle for rights of the meta cultural disputes becoming apparent in and through that struggle and of the tensions resulting from the hegemonic attempt to equalize different economies of value and affection and regimes of historicity. Once the main paradoxes of patrimonialization processes are presented, their unintended consequences and perilous effects are analyzed in three steps. First, a critical reading of the contemporary governmentality is advanced as far as the definition of patrimony is concerned. Second, Mapuche participation in the commemoration of the fortieth anniversary of the last military coup in Bariloche is analyzed, as to identify predicaments resulting from the clash of patrimonializations that focus upon the same event, from perspectives that make different critical comments on history, the places of memory and the environment. Once the instabilities of meanings that the event made apparent are identified, alternatives are explored to walk through these “minefields”, inherited from previous wars and current skirmishes.